Analisis Kebutuhan Pengembangan Model Team-Based Project–Flipped Classroom dalam Pembelajaran Penulisan Ilmiah di Perguruan Tinggi - Noni Febriana; Wienda Gusta Wienda Gusta; Afnesha Noveriana Chang Afnesha Noveriana Chang (Fakultas Sastra Universitas Ekasakti, 2026)
The ability to write scientific papers is an important competency that students must possess. However, teaching scientific writing in universities still faces various obstacles, such as students' poor ability to develop ideas, understand the structure of scientific papers, and apply theory to writing practice. This study aims to analyze the need to develop a Team-Based Project–Flipped Classroom (TBP-FC) model for teaching scientific writing in universities. The study used the Research and Development (R&D) method with the ADDIE model in the needs analysis stage. The study subjects consisted of 30 students and lecturers teaching Indonesian Language at Putra Indonesia University (YPTK) Padang. Data were collected through questionnaires and interviews. The results indicate that students require a learning model that is interactive, flexible, can be studied independently, and can help them understand the scientific writing process more effectively. Furthermore, lecturers also require a learning model that can increase student engagement in the learning process. The findings also reveal that existing learning methods are still predominantly teacher-centered and have not fully facilitated collaborative learning, critical thinking, and independent learning skills. Students expressed a strong need for learning materials that are accessible anytime and anywhere and support project-based activities. Based on the needs analysis, the Team-Based Project–Flipped Classroom model is deemed relevant for development as a solution for teaching scientific writing in universities.